Single‐Cell Tracking: A New Microengineered Platform for 4D Tracking of Single Cells in a Stem‐Cell‐Based In Vitro Morphogenesis Model (Adv. Mater. 24/2020). Issue 24 (16th June 2020) - Samal, Pinak; Maurer, Philipp; van Blitterswijk, Clemens; Truckenmüller, Roman; Giselbrecht, Stefan
Abstract : In article number 1907966, Stefan Giselbrecht and co‐workers describe a new multifunctional microengineered platform to study patterning in free‐floating 3D stem cell aggregates. The platform synergistically combines controlled 3D cell culture in tailored microwells with an open‐source image analysis pipeline to track real‐time aggregate morphogenesis at cellular resolution.